Are Crypto-Assets More Resilient to Financial Shocks than Conventional Assets? - Steli, El Mehdi; Ouchen, Abdessamad (Theoretical and Practical Research in Economic Fields, 2026)
This article examines the resilience of crypto-assets and that of conventional assets to financial shocks. It uses GARCH models to analyze the volatility of daily returns of crypto-assets (i.e., BTC, ETH, BNB, XRP, ADA) and conventional assets (i.e., AAPL, MSFT, GOOG, AMZN, NVDA), with their respective benchmarks (i.e., CRIX and S&P500). The total study period runs from March 16, 2018, to June 30, 2023, divided into three sub-periods: the pre-COVID-19 period (March 16, 2018, to November 29, 2019), the post-COVID-19 period (December 02, 2019, to February 09, 2022), and the Russo-Ukrainian war period (February 10, 2022, to June 30, 2023). The results indicate that crypto-assets are more volatile than conventional assets over the full study period, confirming their status as risky assets. Furthermore, all assets experienced a significant increase in volatility during the COVID-19 pandemic, with particularly high levels for crypto-assets compared to conventional assets. During the Russo-Ukrainian war period, crypto-assets experienced high levels of volatility, which were slightly lower than those observed during the post-COVID-19 period. Compared to crypto-assets, conventional assets are more resilient to financial shocks. Our research could help investors build their portfolios while also allowing them to understand the role of digital assets in risk management.